ASEAN’s Role in Protecting Migrant Workers’ Rights During the Covid-19 Pandemic - Budi Hermawan Bangun (Universitas Negeri Semarang, 2022)
This paper focuses on ASEAN’s efforts as a regional organization to protect the rights of migrant workers in the Covid-19 pandemic situation. The protection of the rights of migrant workers is part of the protection of human rights regulated in various international legal instruments as well as within the ASEAN framework, especially in the ASEAN Consensus on the Promotion and Protection of the Rights of Migrant Workers (ACPPRMW). Although responding quickly to the impact of the Covid-19 pandemic on the economic and health sectors, ASEAN’s response and efforts in protecting the rights of migrant workers during the Covid-19 pandemic were late and ineffective. This is also an illustration of the ineffective implementation of the system and mechanism for the protection of migrant workers in ASEAN as well as the implementation of other ASEAN human rights legal instruments, due to the main principle that is firmly held by ASEAN, namely the non-interference principle.